Auditoría en seguridad vial vía Obando – Zaragoza, tramo Km 66+000 al Km 75+000 (2023)
The study was made to complete a road safety audit (ASV) on the factors: signaling, containment barriers, geometric design of the road and speed, in order to establish comparable conditions to the flow of passengers on it, in the included segment, from the beginning of the part of the variation of the Obando – Zaragoza road, section Km 66+000 to Km 75+000.